Studi Eksploratif Mengenai Yogyakarta sebagai Pengirim Wisatawan Keluarga - Wardiyanta Wardiyanta; Sudarmadji Sudarmadji; Nopirin Nopirin (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2016)
Family recreation is becoming more popular among families in Yogyakarta. This phenomenon is associated with an increased understanding of the importance of family togetherness, strengthen family ties and family memories. The practice of family recreation is affected by geographic, demographic changes, and understanding of the importance of tourism for the family. The purpose of this study is to explain the tendency of families's understanding of family recreation and trend of family recreation. The findings suggest that family recreation associated with increased understanding and mobility of families. This study contributes to an understanding of the social changes in Yogyakarta families and its meaning for the tourism industry in the future.